ASSESSING TECHNICAL FEASIBILITY AND ACCEPTABILITY OF PROVIDING TELEHEALTH PALLIATIVE CARE IN NURSING HOMES. (11th November 2018) - Wertz, V; Bui, N; Uy, E; Barrientos, P; David, D; Lee, S J; Ritchie, C; Stephens, C
Abstract: Use of telehealth to provide NH palliative care(PC) has been extremely limited, only focusing on end-of-life care. No studies have examined how it can be used to proactively deliver PC expertise/support to NH residents, families, and staff. We conducted 6 feasibility tests of telehealth PC in 3 NHs with 19 residents, families, providers and staff (53% female, 47% white, 79% age 50+). None had prior experience with telehealth. 100% were comfortable with the video visit and could see themselves using it in the near future (74% for own care; 90% for family care). 84% strongly believed technology could improve communication between patients/families/providers; 74% strongly believed technology could improve care coordination between NHs and hospitals. 37% rated audio quality fair, 63% good/very good. 47% rated visual quality fair, 47% good/very good. NH telehealth PC is technically feasible and acceptable, providing an innovative opportunity to improve access to needed NH PC services/supports.